Investigation of the Penetration Force of Disposable Sterile Needles through Biomedical Textile Surfaces - Kayahan, Ersin; Ozbey, Sayit; Kosa, Ugur; Ilgaz, Mehmet Alp; Corovic, Selma (Engineering, Technology & Applied Science Research, 2023)
Disposable sterile needles are essential highly consumed medical tools. Medical needles are usually manufactured according to standardized protocols, which currently do not provide the specified minimum tolerance value of the penetration force which strongly depends on needle dimensions, needle cutting edge angle, and the type of the tissue surface to be penetrated. In the present study, experimental measurements were performed according to the ISO 7864 standard to investigate the needle-surface penetration effect via the experimental assessment of the influence of the needle dimensions, cutting edge angle, and three different types of biomedical textiles/artificial tissues (i.e. polyurethane (PU), polypropylene (PP), and artificial leather (AL)) on the penetration force. The results indicate that the smaller the needle’s cutting-edge angle, the smaller the penetration force across the target tissue surface. An exponential decaying relationship has been found between the penetration force and the needle diameter/gauge. The results also show that PP provides similar results to other materials that are already included in ISO 7864, and it has a good potential to be accepted as a standardized biomedical textile.